Neuromodulatory Effects Induced by the Association of Moringa oleifera Lam., Tribulus terrestris L., Rhodiola rosea Lam., and Undaria pinnatidifida Extracts in the Hypothalamus - Chiavaroli, Annalisa; Di Simone, Simonetta Cristina; Acquaviva, Alessandra; Nilofar, Nilofar; Libero, Maria Loreta; Brunetti, Luigi; Recinella, Lucia; Leone, Sheila; Orlando, Giustino; Zengin, Gokhan; Di Vito, Maura; Menghini, Luigi; et al. (Chemistry & biodiversity, 2024)
The present study investigated the role of a commercial formulation constituted by herbal extracts from Rhodiola rosea, Undaria pinnatifida, Tribulus terrestris, and Moringa oleifera. The formulation was analysed for determining the content in total phenols and flavonoids and scavenging/reducing properties. The formulation was also tested on isolated mouse hypothalamus in order to investigate effects on serotonin, dopamine, neuropeptide Y (NPY), and orexin A. The gene expression of gonadrotopin releasing hormone (GnRH) was also assayed. The formulation was able to reduce dopamine and serotonin turnover, and this could be related, albeit partially, to the capability of different phytochemicals, among which hyperoside and catechin to inhibit monoaminooxidases activity. In parallel, the formulation was effective in reducing the gene expression of NPY and orexin‐A and to improve the gene expression of GnRH. In this context, the increased GnRH gene expression induced by the formulation may contribute not only to improve the resistance towards the stress related to ageing, but also to prevent the reduction of libido that could be related with a stimulation of the serotoninergic pathway. According to the in silico analysis, hyperoside could play a pivotal role in modulating the gene expression of GnRH. Regarding NPY and orexin A gene expression, no direct interactions between the formulation phytochemicals and these neuropeptides were anticipated; thus, suggesting that the pattern of gene expression observed following exposure of the hypothalamus to the formulation may be secondary to inhibitory effects of dopamine and serotonin turnover. Concluding, the present study demonstrated the efficacy of the formulation in exerting neuromodulatory effects at the hypothalamic level; thus, suggesting the potential to contrast stress and fatigue.